INTEGRATIVE FACTORS OF BRIDGE SIMULATOR LABORATORY ADAPTION : BASED PROJECT MODEL - Anton Novianto; Dwiza Riana (LPPM STMIK Pringsewu, 2023)
One of the learning models that are often used and developed is PjBL (Project Based Learning). PjBL is a teaching approach built on learning activities and real tasks that provide challenges for learners related to everyday life to solve in groups (Goodman and Stivers 2010). Bridge Simulator is one of the supporting suggestions in implementing PjBL in vocational learning, which has become a national and international standard regulated by the Ministry of Transportation and IMO (International Maritime Organization), where users/students can apply the PjBL method with the BRM (Bridge Resource Management) concept. The focus of this study is how the adaptation of learning models with simulators by school residents including students, measurements using the DM model and TTF model, that the adaptation of simulator learning shows positive results.